The beguiled (1971) [videorecording (DVD)] - Eastwood, Clint, 1930-; Page, Geraldine; Hartman, Elizabeth, 1943-1987; Cullinan, Thomas (Universal Home Video, 1998)
A wounded Union soldier is taken in by the women at a girl's school in the South. He manages to seduce both a student and a teacher, and jealousy and revenge ensue.